TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN (TJSL) ENERGI MEGA PERSADA - Rika Juliana; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study berjudul Social and Environmental Responsibility (TSLE) Energi Mega Persada MALACCA STRAIT S.A. in the villaga district of Merbau the pacific gulf islands district meranti. This study aimed to decribe the characteristics of families that Energi Mega Persada MALACCA STRAIT S.A trahid up communoties in the pacific bay village district Merbau district Kepulauan Meranti. Methods of data analysis quantitatively tells the results of studies used in this study is the menthod census inused as a sample in order fo get 20 samples. Research was conducted in the village of bay islands of the diistrict Merbau Meranty. Resultsof the study characteristics of families who get help from the CSR program is being study level, ie the religion of islam, the number of dependents average 3-6, the results obtained for himselft or his family and kept unutuk capital loan respoyment (capital bagi meminjam di LKM). Middle economic levels. Then the parents want their children to school are at the highest.parents conssider the child and the caregiver also provide axcitement when all the children’s needs are met, childrents feel burdened because of the greater costs incurred after having chidren, elderly people feel freedom possessed reduced and parents become more tored parents become more tired whentaking care of children because many karena additional. The impact of CSR programs conducted Energi Mega Persada Malacca Strait S.A yaitu peningkatan in improving the living standatd of their economic income can rise of the target CSR havng respective fields of expertise such as brownies membuat sago, sago noodles, crackers sago, sago dry cendol, sago cake dry and has a small shop. They benefit from CSR programs because it can improve the welfare of the familiy.Keywords: Social, Environmental, Responsibility